The first illustrations of male external genitalia of sixty species belonging to digger wasps (Hymenoptera: Apoidea). (2nd October 2022) - Kaplan, Emin
ABSTRACT: The male external genitalia of 60 species belonging to 25 genera of six families (Astatidae, Bembicidae, Crabronidae, Pemphredonidae, Philanthidae and Psenidae) of digger wasps are illustrated for the first time. The paper includes detailed descriptions of the genital structures and describes the differences and similarities between genera and species.